ChemInform Abstract: Transition‐Metal Controlled Diastereodivergent Radical Cyclization/Azidation Cascade of 1, 7‐Enynes. Issue 40 (September 2016) - Zhao, Yingying; Hu, Yancheng; Wang, Haolong; Li, Xincheng; Wan, Boshun
Abstract: Optimized reaction conditions employing copper or manganese salts allow the selective formation of cis‐ or trans‐fused pyrroloquinolinone from 1, 7‐enynes.